Sales technology usage: Modeling the role of support service, peer usage, perceived usefulness and attitude. Issue 1 (8th January 2018) - Upadhyay, Ashwani Kumar; Khandelwal, Komal; Nandan, Tanuj; Mishra, Prashant
Abstract : Purpose: The purpose of this paper is to model the key influencers or predictors for usage of technology by sales professionals in India. Design/methodology/approach: This study examines the effect of individual, organizational and social factors on the use of technology. The method used for primary research is survey, and data have been collected from 556 sales professionals from across four industries in India. The empirical analysis consists of confirmatory factor analysis using structural equation modeling. Findings: Confirmatory factor analysis has been used to validate the constructs, namely, peer usage, support service, perceived usefulness, attitude, usage and performance. Based on the results, it has been concluded that attitude and peer usage have a direct effect on the use of technology. Support service affects peer usage and perceived usefulness affects attitude. This model helps us understand the direct and indirect predictors of use of sales technology (ST), and its effect on sales performance. Research limitations/implications: The limitation of this study is that data pertain to India only. Practical implications: The findings of this paper will help sales managers and organizations develop strategies to increase the acceptance and use of new technologies, and also strengthen their arguments for convincing the various stakeholders about the benefits and relevance of the ST. Originality/value: The paper attempts to build and validate a parsimonious model taking into account peer usage (social factor) and support service (organizational factor) in addition to perceived usefulness and attitude.